Perhitungan Rencana Anggaran Biaya Terhadap Struktur Gedung Hotel Nunusaku Di Wilayah Kota Ambon - Semuel Huwae; Herry Henry Roberth; Vector R. R. Hutubessy (Universitas Pahlawan Tuanku Tambusai, 2025)
Hotels are also one of the complex types of buildings in terms of design, construction and cost. Before starting the construction of a hotel, it is important to have a clear understanding of the cost budget required for the structure of the building, including structural aspects such as foundations, walls and roofs. The purpose of this study is to determine the volume of each work item, determine the value of the cost budget plan required for the construction of the Nunusaku Hotel building and the estimated time for the implementation of the construction of the Nunusaku Hotel building.The methods used in this study are literature and quantitative methods. The literature method is by using the literature method, in collecting data and information through books and references as well as internet media in the design of RAB. The data collection method is in the form of a basic price. In the calculation of the Nunusaku Hotel Building Cost Budget Plan, using Work Unit Price Analysis (AHSP) for the Ministry of Public Works Cipta Karya Sector on 2023, and using the unit price of wages and materials for the city of Ambon in 2023.Based on the results of the calculation of the Nunusaku Hotel Building Cost Budget Plan, the value of the cost budget plan was obtained of Rp. 1,992,254,000.00 (One Billion Nine Hundred Ninety Two Million Two Hundred Fifty Four Thousand Rupiah), the implementation time required for the construction work of the structure of the Nunusaku hotel building is 24 weeks (6 months.)